Fabrication and characterization of BMI specimens by DMA tests - Tan, Zhen Wei (2014)
Composite materials have begun to gain recognition in the aviation industry due to their excellent strength to weight ratio. Bismaleimides composites are slowly replacing epoxy composites. This study will provide a framework for fabricating test specimens samples by detailing procedures and equipment required. The material used for this test is 4,4’-bismaleimidodiphenylmethane combined with o,o’-diallylbisphenol A which is a common bismaleimide resin currently available in the market.